Influences of Mn doping on the microstructural, semiconducting, and optoelectronic properties of HgO nanostructure films. Issue 8 (20th February 2019) - El‐Hagary, Magdy; Moustafa, Said H.; Hashem, Hany; Shaaban, Essam R.; Emam‐Ismail, Mohamed
Abstract: Mn‐doped HgO nanostructured thin films (Hg1‐x Mnx O) have been prepared using electron beam evaporation technique on Corning glass (1022) substrate at room temperature with different concentrations x = 0, 0.015, 0.05, 0.1, 0.15, and 0.2. The microstructural, morphological, semiconducting, and optoelectronic properties of the films have been investigated. The X‐ray diffraction spectra suggest a hexagonal wurtzite type structure with lattice parameters decreased with increasing Mn content. It was found that the average particle size of the films decreases with increasing Mn doping which is confirmed by FE‐SEM and AFM micrographs. The optical band gap of the investigated Mn‐doped HgO nanocrystalline films is determined from the absorption coefficient and found to increase with the increase of Mn concentration which is attributed to the sp‐d exchange interaction and/or the quantum confinement effect. The refractive index and extinction coefficient of the Mn‐doped HgO films are also reported. The refractive index dispersion n( λ ) is analyzed by single‐effective‐oscillator dispersion model proposed by the Wemple–DiDomenico (WDD). The oscillator parameters were estimated. The obtained dispersion values are suitable for the design of optoelectronic devices.